Ethanolic extract of the Centella asiatica (L.) Urb. leaf decreases cerebellar brain-derived neurotrophic factor (BDNF) levels in rats after chronic stress - Dwi Cahyani Ratna Sari; Desby Juananda; Mawaddah Ar-Rochmah; Muhammad Mansyur Romi; Nur Arfian (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Chronic stress produces glucocorticoid-induced neurotoxicity that may lead to alterations of the brain-derived neurotrophic factor (BDNF) concentration in the brain. Cerebellum is known to be severely affected by glucocorticoids-associated oxidative damage. Centella asiatica (L.) Urb. may protect neurons from oxidative damage. This study aimed to investigate the effect of ethanolic extract of C. asiatica (L.) Urb. leaf on the rat cerebellar BDNF levels following stress. Twenty young-adult male Sprague Dawley rats were randomly assigned into four experimental groups. The stress control group received aquadest, and the other groups were treated with different doses of the C. asiatica (L.) Urb. extract i.e 150 (CeA150), 300 (CeA300) and 600 (CeA600) mg/kg body weight/day orally, respectively and followed by chronic footshock stress for 28 days. Upon completion of the experimental period, all animals were sacrificed and the cerebellar was isolated. The BDNF levels from the cerebellar tissue lysate was measured using ELISA. The mean BDNF levels of the cerebellar tissue in the stress control, CeA150, CeA300 and CeA600 groups were 1217.10±301.40; 771.46±241.45; 757.05±268.29; and 627.00±246.02 pg/mL, respectively. Post-hoc analysis showed a significant difference between the control and treatment groups (p< 0.05). In conclusion, the ethanolic extracts of the C. asiatica (L.) Urb. leaf decrease the cerebellar BDNF levels in rats after chronic stress.